2018
DOI: 10.1002/jcb.26551
|View full text |Cite
|
Sign up to set email alerts
|

High levels of extracellular ATP lead to chronic inflammatory response in melanoma patients

Abstract: Skin cancer represents a serious public health problem and melanoma is considered the most significant due to its high metastasis capacity. Evasion mechanisms are the main characteristic of these tumor cells to escape of immune response. Extracellular nucleotides and nucleosides play an important role in inflammatory and immune responses. In this study, we analyzed the expression and activity of purinergic system enzymes in platelets and lymphocytes, ATP levels quantification, as well the level of pro and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
0
14
0
3
Order By: Relevance
“…[ 38 ] The wound microenvironment after tumor excision is usually a chronic inflammatory microenvironment, and high levels of ATP in the microenvironment induce macrophages to release large amounts of pro‐inflammatory factors. [ 16 ] It has been reported that gap junction molecular Cx43 can affect host inflammation responses and cell migration during wound healing. [ 39 ] Connexin hemichannels are important channels for ATP releasing in many cells, including inflammatory cells, endothelial cells, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 38 ] The wound microenvironment after tumor excision is usually a chronic inflammatory microenvironment, and high levels of ATP in the microenvironment induce macrophages to release large amounts of pro‐inflammatory factors. [ 16 ] It has been reported that gap junction molecular Cx43 can affect host inflammation responses and cell migration during wound healing. [ 39 ] Connexin hemichannels are important channels for ATP releasing in many cells, including inflammatory cells, endothelial cells, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of extracellular ATP induce macrophages to initiate an immune response and release a large number of inflammatory factors, which may lead to tumor recurrence. [ 16 ] Thus, modulating the ATP release from cells may be a feasible way to control the inflammation responses in the wound sites. It has been reported that JM2 could reduce the concentration of extracellular ATP.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic chain responsible for ATP hydrolysis and adenosine production, present in all immune and vascular cells, has an important role in the control or promotion of inflammation in tumors [ 117 ]. This is because of an exuberant immune/inflammatory response, not adequately balanced by endogenous mechanisms of homeostatic control that can lead to persistent and abnormal forms of collateral tissue damage [ 118 ].…”
Section: Noncommunicable Neurological and Degenerative Diseasesmentioning
confidence: 99%
“…The molecules, receptors and ectoenzymes of the purinergic system could be an alternative measure regarding the process of combating graft rejection, since this system has important participants in metabolic processes, such as inflammatory and immunological responses [4][5][6]. Extracellular adenosine triphosphate (ATP) is either passively released by necrotic cells during cell damage, or it is actively released by activated immune cells and by apoptotic cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…ATP is mainly associated with pro-inflammatory response; however, adenosine has opposite effects, limiting inflammation by suppressing the actions of immune cells [4,[12][13][14][15][16]. Knowing that the purinergic signaling is involved in the inflammatory response that leads to acute kidney rejection and chronic allograft dysfunction, we evaluated the modulation of purinergic signaling components in patients after kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%